2007
DOI: 10.1021/jf071680t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Cooking Conditions on Bioactive Compounds Present in Broccoli Inflorescences

Abstract: Cooking as a domestic processing method has a great impact on food nutrients. Most Brassica (Brassicaceae, Cruciferae) vegetables are mainly consumed after being cooked, and cooking considerably affects their health-promoting compounds (specifically, glucosinolates, phenolic compunds, minerals, and vitamin C studied here). The microwave cooking process presents controversial results in the literature due to the different conditions that are employed (time, power, and added water). Therefore, the aim of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 39 publications
4
43
0
4
Order By: Relevance
“…Vallejo et al(2002) reported that cooking by microwave resulted in high losses of both aliphatic and indole/aromatic glucosinolates in broccoli. The high rate of water evaporation leaching the glucosinolates from the broccoli florets might explain those dramatic losses (López-Berenguer et al, 2007), which is consistent with our findings. On the contrary, Verkerk and Dekker (2004) reported an increase (about 78%) in total glucosinolate content in red cabbage after microwave cooking and it might be an result due to an increase on the chemical extractability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Vallejo et al(2002) reported that cooking by microwave resulted in high losses of both aliphatic and indole/aromatic glucosinolates in broccoli. The high rate of water evaporation leaching the glucosinolates from the broccoli florets might explain those dramatic losses (López-Berenguer et al, 2007), which is consistent with our findings. On the contrary, Verkerk and Dekker (2004) reported an increase (about 78%) in total glucosinolate content in red cabbage after microwave cooking and it might be an result due to an increase on the chemical extractability.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of ascorbic acid (the predominant form of vitamin C) in broccoli generally was decreased after cooking (Serrano et al, 2006). Previous studies have shown that boiling and microwaving caused a great loss of vitamin C (López-Berenguer et al, 2007;Sikora et al, 2008;Vallejo et al, 2002). Our study also shows that boiling and stir-frying/boiling caused a dramatic loss Hudson et al(1985) and Vallejo et al (2002) reported that steaming caused less loss of vitamin C than boiling and microwaving, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we focused on raw materials and their variation within crops. But there are other factors affecting the mineral concentration of these crops, such as cooking including the loss in cooking water (López-Berenguer et al, 2007). Therefore, these factors will also need to be considered to determine nutritional value based on mineral content.…”
Section: Resultsmentioning
confidence: 99%